Employee Creativity and Innovation: The Influence of Leadership Style, Public Service Motivation and Mediating Role of Psychological Empowerment - Ganeva, Irvan; Savitri Pusparini, Elok (Jurnal Manajemen dan Organisasi, 2024)
Creativity and innovation are essential for enhancing public sector organizations and services. Given the hierarchical structure of public sector entities, leadership and employee motivation play a pivotal role in cultivating creativity and innovation. This study examines the effects of leadership styles such as transformational (TF), transactional (TSC), servant (SL), authentic (AL), and authoritarian (AU), along with public service motivation (PSM) on employee creativity and innovation (CI), through mediating psychological empowerment (PSE). Data obtained from 454 civil servants at Indonesia’s Ministry of Manpower were analyzed using Covariance-Based Structural Equation Modeling (CBSEM). This study discovered that TF, SL, and AU, along with PSM, positively influence creativity and innovation through PSE. Conversely, TSC and AL do not have a notable impact. This study contributes both theoretical and practical contributions to the field of human resources and organizational development, by providing empirical evidence and deeper insights into the determinants of employee creativity and innovation.